XII Allemandes pour le pianoforte par Louis van Beethoven. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::: (2022)
Manuscript copy of Beethoven's German Dances, WoO 8, arranged for piano solo; possibly copied from the edition by J.J. Hummel in Berlin, published ca. 1805. Written in brown ink on ten-stave paper with watermark of a circled horse below a crest, the letters AV[?] below.